FITNESS NON-RESPONSE FOLLOWING AEROBIC EXERCISE TRAINING IN OBESE AFRICAN AMERICANS - Hammond, Macon Travis (East Carolina University, 2020)
Cardiorespiratory fitness (CRF) has been closely associated with cardiovascular disease (CVD) and all-cause mortality. An inverse relationship between CRF, and CVD and all-cause mortality has been well-established. To decrease the risk of developing CVD and all-cause mortality, aerobic exercise is prescribed as a preventative measure. Most individuals exhibit increases in CRF, and subsequent CVD and mortality risk reduction, following engagement in aerobic exercise in accordance with current physical activity guidelines. However, a percentage of individuals have been shown to exhibit an atypical response to exercise when considering CRF. This group of individuals demonstrate attenuated responses or adverse responses to exercise even after following aerobic exercise prescribed in concert with current physical activity guidelines. Additionally, CRF non-response has been reported to be a possible health disparity between African Americans and other races when comparing non-response prevalence following aerobic exercise. As a result, these individuals do not reap the well-documented benefits of aerobic exercise, specifically CVD and all-cause mortality risk reduction. The objective of this study was to examine the prevalence of CRF non-response following moderate and high intensity aerobic exercise in obese African Americans. We examined obese African American participants as part of the High Intensity exercise to Promote Accelerated improvements in Cardiorespiratory fitness (HI-PACE) study. Participants were randomized to a control group or one of two supervised exercise intervention groups for 24 weeks. CRF non-response was defined as a VO2 response of ≤ 0 L/min or ml/kg/min following aerobic exercise, while CRF non-response was defined as a VO2 response of > 0 L/min or ml/kg/min following aerobic exercise. Participants were further classified into responders or non-responders based on follow-up measures at the 12-week mid-intervention mark. A total of 33 participants (mean age=48.8 ± 7.6 years; 75.8% females) were examined for the purpose of this study. When comparing the exercise training groups, both the moderate and high intensity groups demonstrated increases in overall CRF levels. When comparing follow-up values to baseline values within the CRF responder group, significant improvements were elicited in systolic and diastolic blood pressures, and in estimated metabolic equivalents (METs). Additionally, the data trends indicated that high intensity exercise elicited higher CRF increases and clinically significant MET increases when compared to the moderate intensity group although statistical significance was not achieved. No significant differences were observed when comparing follow-up values and change scores between responder and non-responder groups. Based on the results, it may be concluded that both moderate and high intensity aerobic exercise training is effective at increasing overall CRF levels. Additionally, high intensity exercise may be slightly more effective at increasing CRF and eliciting clinically significant MET increases.
Keywords: Cardiorespiratory fitness; non-response; physical activity; obese; African Americans--Health and hygiene; Aerobic exercises; Heart--Diseases--Research; Cardiorespiratory fitness